Isolation and characterization of infectious Vibrio parahaemolyticus, the causative agent of AHPND, from the whiteleg shrimp (Litopenaeus vannamei) - López-León,Patricia (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2016)
Vibrio parahaemolyticus, the causative agent of acute hepatopancreatic necrosis disease (AHPND), was isolated from the hepatopancreas of moribund whiteleg shrimp of commercial farms from Guasave, Sinaloa, Mexico. The isolates were screened on thiosulfate citrate bile salt sucrose agar plates for the selection of green colonies and further characterized through PCR with AP3 primers, 89F/R primers, hemolysin genes, hemolytic and enzymatic activity, hydrophobicity, autoaggregation, and biofilm formation. Bioassays by immersion challenge were conducted to confirm the pathogenicity of selected bacterial strains. In addition, the LC50 was calculated for each isolate. All isolates (35) belonged to V. parahaemolyticus, but three isolates did not correspond to strains that cause AHPND since they were negative with 89F/R primers. All isolates were a-hemolytic and showed biofilm formation (from moderate to strong). Isolates were hydrophobic or hydrophilic and showed high autoaggregation capacity. Eight strains did not kill shrimp and eleven were pathogenic, but differences in virulence were found among them perhaps due to α-hemolysis and differences in biofilm formation and hydrophobicity. Therefore, performed characterization may help to understand the pathogenicity of V. parahaemolyticus. Finally, results showed that smaller shrimp are less resistant to V. parahaemolyticus infection.